Efektifitas Variasi Konsentrasi Ekstrak Kulit Pisang Raja (Musa Paradisiaca var. Raja) Sebagai Biolarvasida Culex Sp. - Oetami Leiylla Kurnia; Aries Prasetyo; Tuhu Pinardi; Djoko Windu P. Irawan (Jurnal Higiene Sanitasi, 2023)
Mosquitoes are vectors of disease and nuisance animals where Culex Sp mosquitoes are vectors of filariasis or elephantiasis. Vector control that has been carried out by the community generally uses chemical insecticides where if the use of chemical insecticides is carried out in the long term and continuously it can cause side effects on the environment, besides that it also causes resistance to the vector itself. This study aims to determine the effectiveness of the peel extract of plantain (Musa Paradisiaca var. Raja) as a larvicide on the mortality of Culex Sp. larvae. This research is an experimental research with The Static Group Comparassion Design. Total population and samples were 600 Culex Sp instar III larvae. The sampling method used random sampling method on Culex Sp instar III larvae or at the age of 3-4 days. Data analysis using Anova analysis using the STATA application. The results of the Anova test showed that there were differences in the mortality of Culex Sp with various doses of plantain peel extract (Musa Paradisiaca var. Raja), the highest effectiveness was 84% with an average mortality of 21 Culex Sp larvae, the conclusion of the study from probit analysis with an LC50 (Lethal Concentration) value of 2,969% and the most effective dose to kill Culex Sp larvae was at a dose of 8%.